Bangladesh: civil resistance in the struggle for independence, 1948-1971 - Hossain, Ishtiaq (Lynne-Rienner, 2013)
By taking a longer, historical view of Bengalis' struggle for independence, this chapter focuses on the Bangla language movement and the nonviolent civil resistance of March 1971. Both movements were directed against a government' which repeatedly used violent means of repression against unarmed people.However, the resort to violence failed to strangulate the movements,often backfired,and ultimately proved counter productive in the face of massive nonviolent mobilization. These two movements are viewed as important "shapers" of Bengali national identity and "enablers" of the emergence of a quasi-independent East Pakistan by the time violent struggle broke out on March 25, 1971 ' I91